Current landscape of exosomal non-coding RNAs in prostate cancer: Modulators and biomarkers - Li, Yongxing; Tang, Xiaoqi; Wang, Binpan; Chen, Ming; Zheng, Ji; Chang, Kai (Non-coding RNA research, 2024)
Prostate cancer (PCa) has the highest frequency of diagnosis among solid tumors and ranks second as the primary cause of cancer-related deaths. Non-coding RNAs (ncRNAs), such as microRNAs, long non-coding RNAs and circular RNAs, frequently exhibit dysregulation and substantially impact the biological behavior of PCa. Compared with circulating ncRNAs, ncRNAs loaded into exosomes are more stable because of protection by the lipid bilayer. Furthermore, exosomal ncRNAs facilitate the intercellular transfer of molecules and information. Increasing evidence suggests that exosomal ncRNAs hold promising potential in the progression, diagnosis and prognosis of PCa. This review aims to discuss the functions of exosomal ncRNAs in PCa, evaluate their possible applications as clinical biomarkers and therapeutic targets, and provide a comprehensive overview of the ncRNAs regulatory network in PCa. We also identified ncRNAs that can be utilized as biomarkers for diagnosis, staging, grading and prognosis assessment in PCa. This review offers researchers a fresh perspective on the functions of exosomal ncRNAs in PCa and provides additional options for its diagnosis, progression monitoring, and prognostic prediction. In prostate cancer (PCa), non-coding RNAs (ncRNAs) are transferred from donor cells to recipient cells via exosomes and involved in gene expression through various mechanisms. Due to the regulative effects of exosomal ncRNAs on physiological and pathological processes, they are potential biomarkers and promising therapeutic tools in PCa. [Display omitted]